Berbamine Ameliorates LPS-Induced Inflammation in RAW264.7 Cells and Ovalbumin-Induced Allergic Asthma in Mice - Zhao, Jianlin; Fu, Miaomiao; Sun, Yan (Indian Journal of Pharmaceutical Education and Research)
Background: Asthma is a common and long-lasting respiratory disorder affecting more than 300 million individuals worldwide. Berbamine is a natural and highly active pharmacological compound extracted from the plant Berberis amurensis. Objectives: In our study, we evaluated the potency of berbamine against asthma, a non-communicable chronic lung disease that affects approximately 300 million individuals and is a foremost cause of mortality associated with long-lasting respiratory ailment. Materials and Methods: An in vitro method using RAW264.7 macrophage cells was employed, where allergic conditions were simulated through LPS administration. Before LPS treatment, the cytotoxic effect of berbamine on RAW264.7 cells was examined. Following LPS stimulation in berbamine-treated cells NO, TNF-α, and IL-6 levels were quantified to assess inflammation. Additionally, an allergic asthma model in animals was created through ovalbumin sensitization and treated these animals with berbamine. Results: Eotaxin levels and ovalbumin-specific IgE antibodies were quantified to evaluate the induction of asthma resulting from ovalbumin exposure. Bronchoalveolar lavage fluid was collected to examine the infiltration of total and differential leukocyte counts. Lung weight index, NO, and myeloperoxidase levels in the experimental animals were analyzed to assess berbamine's efficacy against ovalbumin-induced allergic reactions. Oxidative stress and antioxidant levels in the berbamine-treated asthmatic mice was measured. The inflammation-reducing effects of berbamine during ovalbumin sensitization were assessed by quantifying levels of TNF-α, INF-γ, TXB2, and the proinflammatory cytokines IL-6 and IL-12. Furthermore, we explored the efficacy of berbamine in type 2 inflammation by measuring IL-4, IL-5, and IL-13 cytokines. Our results demonstrate that berbamine exhibits a potent anti-inflammatory effect in both asthma models. It effectively attenuated inflammation triggered by LPS stimulation and ovalbumin sensitization, inhibiting cytokines associated with type 2 inflammation. Conclusion: Thus, our findings confirm that berbamine not only reduces inflammatory responses but also mitigates inflammation in allergic asthmatic conditions.
Keywords: Allergic asthma; Phytoalkaloids; Berbamine; LPS stimulation in vitro model; Ovalbumin sensitization in vivo model; Type 2 inflammation.